2013
DOI: 10.1007/s00253-013-4958-y
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of the two-component flavin-dependent monooxygenase from Pseudomonas aeruginosa toward cinnamic acid derivatives

Abstract: 4-Hydroxyphenylacetate 3-hydroxylases (HPAHs) of the two-component flavin-dependent monooxygenase family are attractive enzymes that possess the catalytic potential to synthesize valuable ortho-diphenol compounds from simple monophenol compounds. In this study, we investigated the catalytic activity of HPAH from Pseudomonas aeruginosa strain PAO1 toward cinnamic acid derivatives. We prepared Escherichia coli cells expressing the hpaB gene encoding the monooxygenase component and the hpaC gene encoding the oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 52 publications
3
58
0
Order By: Relevance
“…This stepwise approach was tested due to the possible toxicity of p-coumaric and ferulic acids to the cells [12,[18][19][20][21][22], and because we found that this strategy improved the production of caffeic acid in our previous work (manuscript submitted). However, in the current study the two-step feeding was shown to be counterproductive, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This stepwise approach was tested due to the possible toxicity of p-coumaric and ferulic acids to the cells [12,[18][19][20][21][22], and because we found that this strategy improved the production of caffeic acid in our previous work (manuscript submitted). However, in the current study the two-step feeding was shown to be counterproductive, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The pETDhpaBC plasmid carrying the hpaB and hpaC genes, which was previously constructed, 17) was introduced into Escherichia coli BL21 Star (DE3) cells (Invitrogen, Carlsbad, CA, USA). The transformed E. coli cells were cultivated at 25°C in Luria-Bertani medium, which contained (per liter) Bacto tryptone (10 g), Bacto yeast extract (5 g), and NaCl (10 g, pH 7.0), supplemented with ampicillin (100 μg mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…17,18) The reaction mixture (100 μL) was acidified by the addition of HCl (pH 2-3), and methanol (500 μL) and water (400 μL) were added to the reaction mixture. After vigorous shaking and centrifugation, the resulting supernatant (10 μL) was injected into the HPLC system.…”
Section: Product Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine ammonia lyase and 4-coumarate 3-hydroxylase, encoded by sam8 and sam5, from Saccharothrix espanaensis were used to convert L-tyrosine caffeic acid 4b. 17 pHydroxyphenylacetate (HPA) 3-hydroxylase (HPAH) from E. coli 18 and Pseudomonas aeruginosa 19 can catalyze the hydroxylation of 2-(4-hydroxyphenyl)acetic acid (4-HPA) 2a and pcoumaric acid 4a to 2-(3,4-dihydroxyphenyl)acetic acid (3, 2b and caffeic acid 4b, respectively. However, these enzymatic systems cannot efficiently prepare trihydroxyphenolic acids.…”
Section: ■ Introductionmentioning
confidence: 99%